Effects of aqueous saffron extract on nitric oxide production by two human carcinoma cell lines: Hepatocellular carcinoma (HepG2) and laryngeal carcinoma (Hep2) - Mohamad Reza Parizadeh; Fahime Ghafoori Gharib; Ali Reza Abbaspour; Jalil Tavakol Afshar; Majid Ghayour - Mobarhan (Mashhad University of Medical Sciences, 2011)
Objective: A number of studies have demonstrated the potential antitumor effects of saffron and its constituents on different malignant cells in vitro. It has been reported that a novel glycoconjugate isolated from corms and callus of saffron possesses cytotoxic activity against different tumor cellswith nitric oxide (NO) production. These data suggest that the cytotoxic effect of saffron extract may be related to an effect on nitric oxide production. The aim of the study was to investigate the effect of whole saffron extract on NO production by the hepatocellular carcinoma cell line (HepG-2) and laryngeal carcinoma cell line (Hep-2). Materials and Methods: The cell lines were treated with a saffron extract. The morphologic changes were observed and recorded after 24, 48 and 72 of incubation. The MTT test was used to assess cell viability and the quantitative changes in NO production was evaluated using Griess test in the aforementioned time intervals. Results: The morphologic images showed qualitative changes in both  cell lines. The MTT assay results indicated that there was an increase in cytotoxic effect by adding the extract at concentrations of 0, 200, 400 and 800 µg/ml. However, the NO concentration decreased significantly after 6, 12, 18, 24, 48 and 72 hours of incubation, respectively. IC50 of 400 µg/ml was obtained for HepG2 cells; however, Hep2 and L929 cells did not respond to any extract concentrations. Conclusion: Thisstudy suggested that the saffron extract had a cytotoxic effect on HepG-2 and Hep-2 cell lines. The cytotoxic effect was probably related to a decrease in the NO concentration.